Application of Remote Sensing and Geographic Information System Methods for Land Using Difference - Sukojo, Bangun Muljo; Susilowati, Diah (Makara Journal of Technology, 2003)
Application of Remote Sensing and Geographic Information System Methods for Land Using Difference. Land using difference analysis has been done using remote sensing and Geographic Information System (GIS) methods. Identification of land using difference was conducted using map overlaying process of 1990s (digitized scalling 1:50.000) and 1997s land using map (interpreted from Landsat TM (Thematic Mapper) Image 1997) with UTM (Universal Transverse Mercator) coordinate. Image enhancement was done through histogram equalization with supervised classification devided into 7 classes: rice field, settlement, dry field, industry, pond, sport field and bush. Land using difference and river pollution BOD (Biological Oxygen Demand), COD (Chemical Oxygen Demand) and TSS (Total Suspended Solid) analysis were done through GIS to get database in spasial link and tabular format. Land using difference was done based on division segment of Kali Surabaya contour as reference. The result shows that there were changes on land using from 1990 until 1997 that rice field reduced by 5.72 %; settlement increased by 15,16 %; dry field increased by 0.54 %; industry increased by 36.67 % and bush reduced by 26.67 %. Water pollution analysis results which was done using multiple linier regression show both BOD (determinant coefficient 56 %) and TSS (determinant coefficient 65 %) are affected by difference in land using, but COD (determinant coefficient 24 %) is not affected.